A cost-effectiveness analysis of sotorasib as second-line treatment for patients with KRAS-G12C-mutated metastatic non-small cell lung cancer (mNSCLC) in Switzerland - Tämer El Saadany; Judith Lupatsch; Michael Mark; Michaela Barbier; Tarun Mehra; Matthias Schwenkglenks; Roger von Moos (Swiss Medical Weekly, 2025)
BACKGROUND AND OBJECTIVE: Because of the lack of effective targeted treatment options, docetaxel has long been the standard second-line therapy for patients with advanced non-small cell lung cancer, including the Kirsten rat sarcoma virus (KRAS) G12C mutation. The CodeBreak 200 trial demonstrated that sotorasib, a new drug targeting the G12C-mutated KRAS protein, modestly improved progression-free survival compared with docetaxel in patients whose cancer had progressed after receiving platinum chemotherapy and programmed cell death protein 1 (PD-1) / programmed death ligand 1 (PD-L1) inhibitors as first-line treatment. Consequently, sotorasib received temporary approval in Switzerland.